The MKID Exoplanet Camera for Subaru SCExAO. (17th November 2020) - Walter, Alexander B.; Fruitwala, Neelay; Steiger, Sarah; Bailey, John I.; Zobrist, Nicholas; Swimmer, Noah; Lipartito, Isabel; Smith, Jennifer Pearl; Meeker, Seth R.; Bockstiegel, Clint; Coiffard, Gregoire; Dodkins, Rupert; et al.
Abstract: We present the MKID Exoplanet Camera (MEC), a z through J band (800–1400 nm) integral field spectrograph located behind The Subaru Coronagraphic Extreme Adaptive Optics (SCExAO) at the Subaru Telescope on Maunakea that utilizes Microwave Kinetic Inductance Detectors (MKIDs) as the enabling technology for high contrast imaging. MEC is the first permanently deployed near-infrared MKID instrument and is designed to operate both as an IFU, and as a focal plane wavefront sensor in a multi-kHz feedback loop with SCExAO. The read noise free, fast time domain information attainable by MKIDs allows for the direct probing of fast speckle fluctuations that currently limit the performance of most high contrast imaging systems on the ground and will help MEC achieve its ultimate goal of reaching contrasts of 10 −7 at 2  λ / D . Here we outline the instrument details of MEC including the hardware, firmware, and data reduction and analysis pipeline. We then discuss MEC's current on-sky performance and end with future upgrades and plans.